2006
DOI: 10.22237/jmasm/1146456900
|View full text |Cite
|
Sign up to set email alerts
|

Properties Of Bound Estimators On Treatment Effect Heterogeneity For Binary Outcomes

Abstract: Variability in individual causal effects, treatment effect heterogeneity (TEH), is important to the interpretation of clinical trial results, regardless of the marginal treatment effect. Unfortunately, it is usually ignored. In the setting of two-arm randomized studies with binary outcomes, there are estimators for bounds on the probability of control success and treatment failure for an individual, or the treatment risk. Here, those bounds were refined and the sampling properties were assessed using simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This method can be shown to assume a zero correlation among the potential outcomes, an assumption that we are in fact trying to test by our methods! It has been shown that higher number of clusters and increasing intraclass correlation reduce confidence interval width for existing bounds on treatment risk (Mascha and Albert, 2006). Similar properties were observed for the estimation of treatment risk here, although only variations on the ICC are reported.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…This method can be shown to assume a zero correlation among the potential outcomes, an assumption that we are in fact trying to test by our methods! It has been shown that higher number of clusters and increasing intraclass correlation reduce confidence interval width for existing bounds on treatment risk (Mascha and Albert, 2006). Similar properties were observed for the estimation of treatment risk here, although only variations on the ICC are reported.…”
Section: Discussionsupporting
confidence: 78%
“…As we have shown, and as shown by Mascha and Albert (2006) in their work assessing properties of the AGM bounds, clustering helps to tighten the confidence intervals on bounds and on estimates for the treatment risk and potential outcome correlation. We therefore created the same 40 post-hoc clusters as did AGM using quantiles of the logit score of each individual from a model predicting their observed success on either treatment or control from baseline factors (not including treatment).…”
Section: Data Applicationmentioning
confidence: 63%
See 3 more Smart Citations